PrEP interest and HIV‐1 incidence among MSM and transgender women in coastal Kenya. Issue 6 (13th June 2019) - Kimani, Makobu; van der Elst, Elise M; Chiro, Oscar; Oduor, Clifford; Wahome, Elizabeth; Kazungu, Winston; Shally, Mahmud; Rinke de Wit, Tobias F; Graham, Susan M; Operario, Don; Sanders, Eduard J
Abstract: Introduction: There is emerging data on HIV‐1 incidence among MSM in sub‐Saharan Africa (SSA), but no known estimate of HIV‐1 incidence among transgender women (TGW) in the region has yet been reported. We assessed HIV‐1 incidence and pre‐exposure prophylaxis (PrEP) interest in men who have sex with men exclusively (MSME), men who have sex with men and women (MSMW) and TGW in coastal Kenya. Methods: HIV‐1‐seronegative individuals who had participated in an HIV testing study in 2016 were traced and retested in 2017 according to Kenyan guidelines. All participants were assigned male sex at birth and had male sex partners; additional data on gender identity and sexual orientation were obtained. We assessed the factors associated with HIV‐1 acquisition using Poisson regression and calculated HIV‐1 incidence in MSME, MSMW and TGW. PrEP interest was assessed through focus group discussions to characterize subcategories' perceived PrEP needs. Results: Of the 168 cohort participants, 42 were classified as MSME, 112 as MSMW and 14 as TGW. Overall, HIV‐1 incidence was 5.1 (95% confidence interval (CI): 2.6 to 9.8) per 100 person‐years (PY): 4.5 (95% CI: 1.1 to 17.8] per 100 PY among MSME, 3.4 (95% CI: 1.3 to 9.1) per 100 PY among MSMW and 20.6 (95% CI: 6.6 to 63.8] per 100 PY among TGW. HIV‐1 acquisition was associated with exclusive receptive anal intercourse (aIRR 13.0, 95% CI 1.9 to 88.6), history of an STI in preceding six months (aIRR 10.3, 95% CI 2.2 to 49.4) and separated/divorced marital status (aIRR 8.2 (95%: 1.1 to 62.2). Almost all (98.8%) participants were interested in initiating PrEP. MSME and TGW felt that PrEP would lead to increases in condomless anal or group sex. Conclusions: TGW had a very high HIV‐1 incidence compared with MSME and MSMW. Subcategories of MSM anticipated different PrEP needs and post‐PrEP risk behaviour. Further studies should assess if TGW may have been wrongly categorized as MSM in other HIV‐1 incidence studies in the region.